Estrategias didácticas y el desarrollo de la destreza lectora en los estudiantes del sexto grado A, de la escuela de Educación General Básica (EGB) Teniente Hugo Ortiz, período académico 2018-2019. Lineamientos alternativos - Donoso Calderon, Maria del Cisne (2019)
The present academic research work, Didactic Strategies and the Development of the Reading Skill of students in Class 6 A in the General Basic Education (EGB) Teniente Hugo Ortiz school academic term 2018 - 2019. Alternative guidelines, came up due to the need to improve the reading skill observing that the students of that year have problems to understand, synthesize new knowledge, difficulties to infer, and analyze text selections deserved the questions: What to do to promote reading comprehension? What strategies are feasible to incentive interest for reading? Taking into consideration these questions the objective stated was to analyze the didactic strategies and their application for the development of the students' reading skill. It was sustained by means of the descriptive study and the methods: descriptive, observational, analytic, synthetic, inductive, deductive, hermeneutic; techniques: observation and survey; instruments: observation sheet and questionnaire and the procedures: diagnostic and theoretic foundation, and the design of the alternative guideline taking as reference the diagnosis made on the reading process and development wherein the main problem is the reading comprehension difficulty not having knowledge about didactic strategies and their application as a learning mechanism as a result of students' interest as an outstanding part of the learning process. Twenty-nine students and one teacher was the population involved. Finally, the didactic strategies are influenced in a positive way in the development of reading skills of the students and in the teaching-learning process.